Improving the Learning Results of Indonesian Subject through the Use of Quizizz Media for the Third Graders of Elementary School - Mei Kurnia Fitriani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study is to improve the learning outcomes of the third graders using Quizizz at SD Negeri 3 Kebumen Pringsurat subdistrict Temanggung regency Academic Year 2020/2021. The type of this research is Classroom Action Research (CAR) using Quizizz media with two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The research subjects are grade III students of SD Negeri 3 Kebumen Pringsurat subdistrict Temanggung regency. Data collection techniques is using tests and observations. Data analysis techniques using quantitative data and qualitative data. Based on the results of the study, the average score of the study results in cycle I is 73,33 and completion of 10 students with a percentage of 55,56 %. On the implementation of cycle II measures averaged 78,89 and completed 15 students with a percentage of 83,33 %. The conclusion of this Classroom Action Research is that using Quizizz media can improve the learning outcomes of the third graders of SD Negeri 3 Kebumen.